PEARLS FOR PRACTICE - MANAGING ELDERLY PRESSURE ULCERS IN HOME CARE - Anisah, Siti (Jurnal Luka Indonesia, 2016)
Background. Elderly people frequently have wounds such as pressure ulcers. These occured especially in frail elderly. Patients have pressure ulcers at home need special education and support of nurses or the other caregiver professional health. These patient also taken of efectiveness modern dressing so easier to use and less frequently follow up. The dressing has to be changed less frequently; this means longer periods of rest for the wound, promotes healing, and reduces the risk of potential maceration. It is very important to use modern dressings and methods that provide optimal exudate management and promote natural debridement and wound healing, while ensuring adequate control of bacteria. Aim. Finally, the patient's quality of life is thus improved. Methods. Share an experience reported of 3 cases study of elderly patient with extremely pressure ulcers on her bodies. Results. Modern dressing and approriate nursing wound care had a quality of life for elderly patients and succesfull healing. Conclusion. The foam dressings useful alternative in the treatment of wounds with excessively heavy exudation. The use of foam dressing for 3 weeks on a 4rd degree pressure ulcers with necrotic and a high level of exudate showed the following : foam dressing managed in an optimal way the high level of exudate in the first phases of treatment. There was no leakage from the dressing, and no maceration of the peri- ulcer skin was observed. The autolytic and osmotic debridement were promoted, and necrotic tissue was cleaned from the ulcers. During the next phases of healing, where the amount of exudate decreased, the wound bed did not dry out and granular tissue was given sufficient protection. Healing was promoted and the patient feel comfortable throughout. Family support, enough resources material modern dressing, control good level glucose with self monitoring blood glucose (SMBG) caring all. Family, caregivers and nutritional supported the whole healing procesed. Keywords: Pressure Ulcers, Elderly, Modern Dressing